A Model of Marketing Strategies to Increase New Student Admissions - Rafni Setiyawan; Ika Barokah Suryaningsih; Mochammad Farid Afandi (LPPM Institut Teknologi dan Sains Mandala, 2025)
This study aims to formulate an effective marketing strategy to increase the number of new student enrollments at the Institute of Technology and Business (ITB) Widya Gama Lumajang. Despite having competitive advantages such as affordable tuition fees, a strategic location, and a strong entrepreneurial vision, the institution has experienced a decline in enrollment over the past five years. Using a descriptive qualitative approach, this research employs SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) analyses to identify internal and external strategic factors. Data were collected through in-depth interviews, observations, and documentation involving university leaders, faculty members, current students, prospective students, and parents. The findings indicate that establishing a dedicated digital content team is a top strategic priority, as social media has become the main channel through which prospective students obtain information. Additional recommended strategies include strengthening alumni and parent networks, conducting open-campus promotional events, and transforming the institution into a university to broaden academic offerings. This study concludes that market-oriented and digitally-driven marketing strategies are essential to enhancing the competitiveness of private higher education institutions amid intense educational competition